Overexpression of GOLPH3 Promotes Proliferation and Tumorigenicity in Breast Cancer via Suppression of the FOXO1 Transcription Factor - Zeng, Zhaolei; Lin, Huanxin; Zhao, Xiaohui; Liu, Guanglin; Wang, Xi; Xu, Ruihua; Chen, Kun; Li, Jun; Song, Libing (Clinical cancer research, 2012)
Purpose: Golgi phosphoprotein 3 (GOLPH3) has been reported to be involved in various biologic processes. The clinical significance and biologic role of GOLPH3 in breast cancer, however, remains unknown. Experimental Design: Expression of GOLPH3 in normal breast cells, breast cancer cells, and 6-paired breast cancer and adjacent noncancerous tissues were quantified using real-time PCR and Western blotting. GOLPH3 protein expression was analyzed in 258 archived, paraffin-embedded breast cancer samples using immunohistochemistry. The role of GOLPH3 in breast cancer cell proliferation and tumorigenicity was explored in vitro and in vivo. Western blotting and luciferase reporter analyses were used to investigate the effect of GOLPH3 overexpression and silencing on the expression of cell-cycle regulators and FOXO1 transcriptional activity. Results: GOLPH3 was significantly upregulated in breast cancer cells and tissues compared with normal cells and tissues. Immunohistochemical analysis revealed high expression of GOLPH3 in 133 of 258 (51.6%) breast cancer specimens. Statistical analysis showed a significant correlation of GOLPH3 expression with advanced clinical stage and poorer survival. Overexpression and ablation of GOLPH3 promoted and inhibited, respectively, the proliferation and tumorigenicity of breast cancer cells in vitro and in vivo. GOLPH3 overexpression enhanced AKT activity and decreased FOXO1 transcriptional activity, downregulated cyclin-dependent kinase (CDK) inhibitor p21Cip1, p27Kip1, and p57Kip2, and upregulated the CDK regulator cyclin D1. Conclusion: Our results suggest that high GOLPH3 expression is associated with poor overall survival in patients with breast cancer and that GOLPH3 overexpression increases the proliferation and tumorigenicity of human breast cancer cells. Clin Cancer Res; 18(15); 4059–69. ©2012 AACR.